2020
DOI: 10.3390/rs12172672
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in Boreal Forests Can Be Quantified Using Terrestrial Laser Scanning

Abstract: Terrestrial laser scanning (TLS) has been adopted as a feasible technique to digitize trees and forest stands, providing accurate information on tree and forest structural attributes. However, there is limited understanding on how a variety of forest structural changes can be quantified using TLS in boreal forest conditions. In this study, we assessed the accuracy and feasibility of TLS in quantifying changes in the structure of boreal forests. We collected TLS data and field reference from 37 sample plots in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 58 publications
(106 reference statements)
0
13
0
Order By: Relevance
“…Compared to the use of conventional forest mensuration tools, the point cloud-based methods enable detailed characterization of the 3D structure of trees (e.g., [29,30,35,39]) and their change in time [49]. The results of this study demonstrated that the point cloudbased methods can be successfully utilized also in detecting changes in the stem form and volume allocation of trees, and the validity of the findings were confirmed in different forest conditions.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Compared to the use of conventional forest mensuration tools, the point cloud-based methods enable detailed characterization of the 3D structure of trees (e.g., [29,30,35,39]) and their change in time [49]. The results of this study demonstrated that the point cloudbased methods can be successfully utilized also in detecting changes in the stem form and volume allocation of trees, and the validity of the findings were confirmed in different forest conditions.…”
Section: Discussionmentioning
confidence: 59%
“…Performance of the point cloud processing method used in this study to extract attributes characterizing stem form and volume allocation was validated in [49,51]. The conclusion of the studies was that the forest structure is the most important factor affecting the accuracy of the point cloud-based method.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Terrestrial laser scanning (TLS)-namely, ground-based LiDAR-also offers a detailed 3D representation of the surroundings of forest structures with millimeter accuracy [10,23,24]. Compared to conventional forest inventory tools, such as the use of hypsometers to measure tree height and tapes to measure tree stem diameters [25], the use of TLS point clouds provides non-destructive estimates of stem curve profiles and characterizes the branching structures of trees, thus further improving the modeling of the individual tree volume. TLS data can be collected with either a single-or a multiple-scan mode [24,26].…”
Section: Introductionmentioning
confidence: 99%
“…To relieve these occlusion problems, a plot can be scanned with multiple scans at differ-ent positions instead of a single scan in a fixed position. Yrttimaa et al [25] employed a multiple-scan TLS with point cloud cluster and RANSAC-cylinder filtering algorithms to quantify structural changes in boreal forests in Evo in southern Finland. Their results indicated that multiple-scan TLS has the capacity to characterize trees and forest stands in space and showed that TLS technology could estimate structural changes over time in boreal forests.…”
Section: Introductionmentioning
confidence: 99%